Voice rehabilitation after total laryngectomy using voice prostheses - Staszko, Natalia; Bała, Kamila (Quality in Sport, 2026)
Laryngeal cancer is one of the most common malignant tumors of the upper respiratory tract. Total laryngectomy remains the primary treatment method for its advanced stages. Although the procedure can achieve oncological cure, it leads to numerous multidimensional consequences, the most significant of which is the permanent loss of voice. Voice rehabilitation is a key component of postoperative adaptation, enabling patients to reintegrate into social life. Among the available methods of speech restoration, tracheoesophageal voice prostheses allow for rapid recovery of communication ability, provide the highest quality of substitute speech and significantly improve quality of life. The wide range of available models allows for individualized selection according to patient needs, and the use of automatic speaking valves facilitates hands-free speech. Despite these advantages, the use of voice prostheses is associated with complications that may impair daily functioning and reduce patient comfort. Tracheoesophageal voice prostheses remain the most effective and functionally satisfactory method of post-laryngectomy voice rehabilitation, although their use requires proper care, patient education, and regular medical follow-up to minimize complications. Implementation of timely and individualized voice rehabilitation using tracheoesophageal prostheses plays a crucial role in improving communication, psychosocial well-being, and overall quality of life in patients after total laryngectomy. The aim of this review is to present current methods of post-laryngectomy voice rehabilitation with particular emphasis on tracheoesophageal voice prostheses, considered the gold standard in restoring communication ability.